Male Partners Involvement in Prevention of Mother-to-Child Transmission of HIV Services in Southern Central Ethiopia: In Case of Lemo District, Hadiya Zone - Degefa Tadele Belato; Abera Beyamo Mekiso; Bayu Begashaw (AIDS Research and Treatment)
Male partners’ involvement is a vital issue to prevent human immunodeficiency virus (HIV) transmission from mother to child; because it is much expectable that women were more vulnerable and high risk group of population portion. Therefore, to save lives of mothers and their newborn from acquiring HIV, male partners should do their maximum endeavor regardless of any determinant factors as our results revealed its status in our study context and elsewhere at past time too.